Effects of near shore land-use dynamic on coastal erosion in Phuket, Thailand - Chanida Suwanprasit (2018)
© 2015 IEEE. Land-use change is one of main factors of coastal erosion. This research aimed to integrate techniques of remote sensing and geographic information system to investigate the relationship between land-use changes and coastal erosion in Phuket Island, Thailand, using multi-sensors and temporal imageries acquired during 2003-2011. Eight land-use classes including built-up, forest, mangrove forest, agriculture, aquaculture, water body, beach and other classes were classified using Support Vector Machines (SVMs). Built-up area was the most increasing changed in 2009 (60.29%). The most decreasing changed in 2009 (80%) was beach area. The average erosion rate in Naiyang, Kamala, Patong, Karon, Kata, Katanoi, Naiharn and Rawai beach were 7.90, 13.70, 13.21, 4.72, 11.33, 6.73, 11.63 and 4.75 m/year, respectively. The result showed that increasing of built-up area was significantly related to increasing of coastal erosion significantly. The analytical results can be utilized for coastal managing, monitoring and planning in the future.